2014
DOI: 10.1177/0741932514541485
|View full text |Cite
|
Sign up to set email alerts
|

Using an iPad® App to Improve Sight Word Reading Fluency for At-Risk First Graders

Abstract: Reading proficiency is arguably the most important academic skill needed for school success. Students who fail to acquire basic reading skills in primary grades fall further behind their peers in intermediate and later grades. Despite national efforts to improve academic outcomes for all students, a recent national report in reading (National Center for Education Statistics, 2011) shows that 51% of African American, 49% of Hispanic, and 53% of Native American fourth-grade students were reading below basic lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 20 publications
(27 reference statements)
0
32
1
4
Order By: Relevance
“…There were 64 articles included in the analysis. Musti‐Rao, Lo, and Plati () included two separate studies, resulting in 65 studies total. Among 35 controlled studies, there were more QED studies ( k = 24; 37%) than RCTs ( k = 11; 17%).…”
Section: Resultsmentioning
confidence: 99%
“…There were 64 articles included in the analysis. Musti‐Rao, Lo, and Plati () included two separate studies, resulting in 65 studies total. Among 35 controlled studies, there were more QED studies ( k = 24; 37%) than RCTs ( k = 11; 17%).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies (Cullen, Keesey, Alber‐Morgan, & Wheaton, ; Herbert & Murdock, ; Hilton‐Prillhart, Hopkins, Skinner, & McCane‐Bowling, ; Mechling & Gast, ; Musti‐Rao, Lo, & Plati, ) included students with high‐incidence disabilities (e.g., learning disabilities) and students at risk. Students with low‐incidence disabilities (e.g., developmental disabilities, autism spectrum disorder, and moderate intellectual disabilities) were included in eight studies (Bosseler & Massaro, ; Cazzell et al, ; Crowley et al, ; Ganz et al, ; Lee & Vail, ; Rivera et al, ; Rivera, Hudson, Weiss, & Zambone, ; van der Meer et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with vocabulary words in reading instruction that are mostly unknown or unfamiliar words, sight word is defined as the word “that can be both read and spelled within 2 seconds” (May, , p. 113) such as no, stop, or come back; students are more likely asked to remember the sight words by sight as a whole. Sight word vocabulary was the dependent variable in five (i.e., Cazzell et al, ; Crowley et al, ; Cullen et al, ; Hilton‐Prillhart et al, ; Musti‐Rao et al, ) studies, and content vocabulary was the dependent variable in eight studies (i.e., Bosseler & Massaro, ; Ganz et al, ; Herbert & Murdock, ; Lee & Vail, ; Mechling & Gast, ; Rivera et al, ; Rivera et al, ; van der Meer et al, ). Rivera et al () measured the number of English and Spanish words correct after implementing CAI both in English and Spanish.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that have found drill and practice to be less effective than other teaching strategies, have focused on knowledge that is process based (e.g., addition, or the reading of passages of text) rather than constrained knowledge alone (Musti-Rao et al, 2014;Tournaki, 2003). While there is some criticism for drill and practice (Booker, 2007), when strategically incorporated into a holistic, multi-faceted curriculum that integrates contextualisation, process and knowledge acquisition, drill and practice can facilitate the recall of constrained knowledge, which more cognitively demanding processes of thinking can build upon (Booker, 2007;Pfost et al, 2014;Seaman, 2011).…”
Section: Drill and Practicementioning
confidence: 99%
“…The learning and recall of basic, "constrained" (Pfost et al, 2014, p. 209) knowledge, such as commonly used letter-sound mapping or high frequency sight words can be effectively facilitated via tasks that plan for repeated exposure and rehearsal, often referred to as "drill and practice" (Joseph et al, 2012;Musti-Rao et al, 2014;Yu et al, 2005). Studies that have found drill and practice to be less effective than other teaching strategies, have focused on knowledge that is process based (e.g., addition, or the reading of passages of text) rather than constrained knowledge alone (Musti-Rao et al, 2014;Tournaki, 2003).…”
Section: Drill and Practicementioning
confidence: 99%